Automated synthesis of [18F]Ga-rhPSMA-7/ -7.3: results, quality control and experience from more than 200 routine productions - Alexander Wurzer; Daniel Di Carlo; Michael Herz; Antonia Richter; Stephanie Robu; Ralf Schirrmacher; Alba Mascarin; Wolfgang Weber; Matthias Eiber; Markus Schwaiger; Hans-Juergen Wester (SpringerOpen, 2021)
Abstract Introduction The radiohybrid (rh) prostate-specific membrane antigen (PSMA)-targeted ligand [18F]Ga-rhPSMA-7 has previously been clinically assessed and demonstrated promising results for PET-imaging of prostate cancer. The ligand is present as a mixture of four stereoisomers ([18F]Ga-rhPSMA-7.1, − 7.2, − 7.3 and − 7.4) and after a preclinical isomer selection process, [18F]Ga-rhPSMA-7.3 has entered formal clinical trials. Here we report on the establishment of a fully automated production process for large-scale production of [18F]Ga-rhPSMA-7/ -7.3 under GMP conditions (EudraLex). Methods [18F]Fluoride in highly enriched [18O]H2O was retained on a strong anion exchange cartridge, rinsed with anhydrous acetonitrile and subsequently eluted with a solution of [K+ ⊂ 2.2.2]OH− in anhydrous acetonitrile into a reactor containing Ga-rhPSMA ligand and oxalic acid in DMSO. 18F-for-19F isotopic exchange at the Silicon-Fluoride Acceptor (SiFA) was performed at room temperature, followed by dilution with buffer and cartridge-based purification. Optimum process parameters were determined on the laboratory scale and thereafter implemented into an automated synthesis. Data for radiochemical yield (RCY), purity and quality control were analyzed for 243 clinical productions (160 for [18F]Ga-rhPSMA-7; 83 for [18F]Ga-rhPSMA-7.3). Results The automated production of [18F]Ga-rhPSMA-7 and the single isomer [18F]Ga-rhPSMA-7.3 is completed in approx. 16 min with an average RCY of 49.2 ± 8.6% and an excellent reliability of 98.8%. Based on the different starting activities (range: 31-130 GBq, 89 ± 14 GBq) an average molar activity of 291 ± 62 GBq/μmol (range: 50-450 GBq/μmol) was reached for labeling of 150 nmol (231 μg) precursor. Radiochemical purity, as measured by radio-high performance liquid chromatography and radio-thin layer chromatography, was 99.9 ± 0.2% and 97.8 ± 1.0%, respectively. Conclusion This investigation demonstrates that 18F-for-19F isotopic exchange is well suited for the fast, efficient and reliable automated routine production of 18F-labeled PSMA-targeted ligands. Due to its simplicity, speed and robustness the development of further SiFA-based radiopharmaceuticals is highly promising and can be of far-reaching importance for future theranostic concepts.